Workshop on Creating History Content Videos for High School Teachers in Pemalang, Indonesia - Hartatik, Endah Sri; Utomo, Ilham Nur; Raharjo, Bahagio; Pratama, Olga S.; Ramadhan, Fauzan Syahru; Wasino, Wasino (Journal of Community Empowerment, 2025)
The Deep Learning Curriculum, as the latest educational curriculum, focuses on the application of technology in classroom learning activities for school students, but not all teachers are proficient in its use and application. Therefore, this community service team aims to provide a solution to this problem by holding a workshop on creating historical video content for history teachers in Pemalang Regency. The method used consisted of four stages, namely: 1) observation and problem identification; 2) material preparation; 3) workshop implementation; 4) evaluation. The workshop was held offline at SMA Negeri 1 Bodeh, Pemalang Regency. In the workshop, participants were given an understanding of the local history of Pemalang, techniques for searching for historical sources digitally, types of historical documentary films, and techniques for making historical films based on video editing applications. The workshop results demonstrated that mastering the technological skills needed to create historical video content is crucial for history teachers. This can support the learning process and enhance students' digital literacy skills. Teachers' understanding of historical video content creation technology improved after participating in the workshop. This workshop supports the Ministry of Primary and Secondary Education's program to improve understanding and skills in using technology.